The Effects of Wet Cupping Therapy in Blood Pressure, Glucose, Uric Acid and Total Cholesterol Levels - Sutriyono Sutriyono; Muhammad Rodham Robbina; Meksianis Zadrak Ndii (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2019)
Wet cupping therapy is a simple, cheap, and effective alternative medical treatment. In China wet cupping therapy become a formal treatment in the hospital. 14 centuries ago Prophet Muhammad implemented wet cupping therapy or hejamah as a curing treatment and become sunnah for muslim. Today in a modern world, many studies proved the advantages of wet cupping therapy, which is a sunnah since 14 centuries ago. The aims of this study were to measure the effects of wet cupping therapy treatment on blood pressure, blood glucose, uric acid, and total cholesterol level. 21 participants were treated with hejamah/wet cupping, blood pressure and blood samples were collected from all the participants one week before and one week after hejamah. Blood pressure, either systolic or diastolic was significantly decreased following therapy (p|<|0.05), blood glucose had a slight decreased but not significant (p|>|0.05). uric acid and total cholesterol level was also significantly decreased following therapy (p|<|0.05). With only just one time treatment, hejamah had a significant effects on blood pressure, uric acid and total cholesterol level, that is proved the advantages of hejamah.